LABOUR MARKET IN A TIME OF CRISIS. WHAT DO HR EXPERTS SAY ABOUT THE IMPORTANCE OF DIGITALIZATION IN THE POSTPANDEMIC CONTEXT - Tomina SAVEANU; Sorana SĂVEANU; Raluca BUHAȘ; Claudia BACTER (Annals of the University of Oradea: Economic Science)
For several years we are facing the Fourth Industrial Revolution, or Industry 4.0 as it is also called, which puts its mark across every aspect of our societies. The job market is probably the sector which mostly has to defy the challenges imposed by new technologies and digitalization. Moreover, the COVID19 pandemic majorely impacted the world and, implicitly, the work and the labour market. In order to keep their jobs safe, in a post-pandemic digitalized world people need to focus more and more on developing 21st century skills. The present paper presents an image of a digitalized labor market before and after COVID-19 pandemic, and focuses on how new technologies, which are more and more integrated into the labor market, affect jobs and force people to shift their attention over again to the development of new skills and competences. Qualitative research data was collected from HR experts in private companies from Oradea. We aim to outline the changes occured on the labour market before and after COVID-19 pandemic with focus on the digitalization of work. We investigate how much emphasis companies put on digitalizing the work, which are the new skills that managers are interested in for their employees, and also what is the strategy managers follow in order to train a highly qualified human resource for a digitalized world. Our results show that there are significant changes on the labor market due to digitization which has accelerated after COVID-19 pandemic, however the changes depend on the field of activity. Companies needed to adapt to the new postCOVID-19 context on the labor market and they restructured their way of organizing their work: technical unemployment, short work schedule, flexible work schedule, remote work. Employers are increasingly looking for candidates who have a good level of training in terms of their digital skills and the candidates themselves are more open to different forms of activities in the digital sphere. The technological evolution which defines the features of Industry 4.0 cannot and should not be stopped while the future of our society encompasses digital and technological development in a higher extent.